NALAR KRITIS POLIGAMI SEBAGAI KEKERASAN DALAM RUMAH TANGGA: (Analisis Terhadap Undang-Undang KDRT Nomor 23 Tahun 2004) - Sugitanata, Arif; Karimullah, Suud Sarim (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2023)
In this paper, the researcher analyses and explains polygamy as a form of domestic violence from the perspective of positive Indonesian law and how it critiques Law No. 1 of 1974 on Marriage by examining Law No. 23 of 2004 on the Elimination of Domestic Violence in Indonesia. Using a literature review, this study found that polygamy carried out without fulfilling the conditions stipulated in the marriage law and Islamic Law Compilation (KHI) can be a form of domestic violence. This is because polygamy committed without the first wife's consent and without regard to the family's welfare can cause injustice and imbalance in the husband-wife relationship and damage the family concerned. Polygamy cases, if associated with Law No. 23 of 2004 concerning the elimination of domestic violence, are a form of psychological violence that can be criminalised and charged with Domestic Violence Law No. 23 of 2004, specifically Article five, which states that "every person is prohibited from committing acts of domestic violence against persons within the scope of their household, whether committed directly or indirectly, to cause pain or misery or suffer physically, sexually, psychologically, and or domestic neglect, including domestic neglect". The criminal penalty can be imprisonment of up to three years or a fine of up to 9 million rupiahs. Suppose the psychological attack causes illness or prevents the victim from doing their job to the extent that their daily activities are disrupted. In that case, they can face imprisonment of up to four months or a fine of three million rupiahs.